EVALUATION OF THE IMPLEMENTATION OF POSYANDU FOR TODDLERS IN THE NEW NORMAL ERA IN PEKALONGAN CITY - Putri Andanawarih; Miftachul Jannah (Jurnal Keperawatan Respati Yogyakarta, 2022)
The Covid-19 pandemic is a health problem that exists throughout the world. Because of the pandemic, community activities are strictly limited in order to prevent more transmission in the community by implementing large-scale social restrictions (PSBB) for 3 months in Indonesia. This situation greatly affects the whole condition of society , both in the socio - economic and health sectors. To overcome this, the government has declared a new normal condition. The new normal condition is a scenario to accelerate the handling of Covid-19 in health and socio-economic aspects. One of the main health sectors is the health of mothers and children, especially children under five. This study uses a qualitative descriptive method with a phenomenological approach, in the form of an evaluation analysis of the implementation of the new normal era of Posyandu for toddlers. The objective to evaluate the services of Posyandu for toddlers in the new normal era with agreement components, door to door and online. This research can contribute to health services, especially the implementation of Posyandu for toddlers in the new normal era. Methods: This research is a qualitative descriptive study with a phenomenological approach, in the form of an evaluation analysis of the implementation of posyandu for toddlers in new normal era. The study showed that the Posyandu services for toddlers were temporarily suspended at the beginning of the Covid-19 pandemic according to the formal letter signed by the Mayor of Pekalongan city, and restarted during New Normal by conducting some trials first through pilots in the green zone area of Covid19. The implementation of Posyandu during the New Normal era needs to comply with the Mayor’s formal letter of the Pekalongan City Health Service regarding the health protocol for the activities of the Posyandu services for toddlers. The conclusion is Posyandu activities for toddlers in the new normal era in Pekalongan City were carried out with the obligation to implement the Covid-19 prevention health protocol according to the direction of the Pekalongan City health department. Keywords: Toddler; Posyandu; New Normal